Abdominal compartment syndrome secondary to sepsis and metastatic neuroblastoma in an infant - Sara Batalha; Anaxore Casimiro; João Estrada; Ana Teixeira; Margarida Santos (Wolters Kluwer Medknow Publications, 2015)
Neuroblastoma is the most common solid tumour in children under 1 year of age. The stage IV-S usually has good prognosis with a high rate of spontaneous regression. However in some patients the massive hepatomegaly requires aggressive therapy. Intra-abdominal hypertension and abdominal compartment syndrome are rare and potentially fatal complications of the intra-abdominal tumours and are usually associated with other co-morbidities such as sepsis. The authors present a 3 month-old child with a stage IV-S adrenal neuroblastoma under chemotherapy admitted to the Pediatric Intensive Care Unit due to hemodynamic instability secondaiy to intra-abdominal hypertension and sepsis. In the first days after admission he presented with abdominal compartment syndrome with hemodynamic, respiratory and renal failure. After the first 3 days under medical treatment to reduce intra-abdominal pressine he stabilized without the need for surgical intervention. We emphasize the role of early diagnosis and intervention to prevent adverse outcomes in critically ill children with intra-abdominal hypertension.